Evoke, don't show: Narration in cinematic virtual reality and the making of Entangled. Issue 1 (1st June 2021) - Weaving, Simon
Over the past three years, cinematic virtual reality (CVR) has emerged as a form of media storytelling that takes advantage of the immersive properties of VR technology. However, as a practice it poses a number of challenges for the writer‐director used to controlling the frame through which the viewer experiences the narrative. This research outlines the making of Entangled (a live-action, stereoscopic, VR experience incorporating ambisonic audio) and reflects on concept development and production decision-making with reference to the emerging body of academic knowledge about cinematic VR, in particular ideas about the position of the viewer and the nature of narration. The research addresses some of the gaps in knowledge in these areas, reconciling theoretical positions with a deep understanding of the realities of production processes.